ADAPTASI DAN VALIDASI SKALA STRATEGI SIBLING CONFLICT - Wulandari, Primatia Yogi; Suminar, Dewi Retno; Hendriani, Wiwin (Faculty of Psychology, Diponegoro University, 2019)
Sibling conflict has some influences on children’s development, positively and negatively. It is not only about the frequency, but also about the strategies used in managing conflict. The main purpose of this study was to adapt and to validate Sibling Conflict Strategy Scale developed by Recchia (2009), so it can be used by parents in Indonesia to identify their children’s strategies. The process of adaptation was guided by the International Testing Commission (ITC) Guidelines model for test adaptation, which include forward – backward translation processes, followed by expert reviews to test language and conceptual equivalence. Then, we conducted the validation process by testing the Content Validity Index (CVI) and Confirmatory Factor Analysis (CFA). Two hundred and six parents in Surabaya who have children in the age range of 52-87 months (M = 71.21) were participated in the pilot study. The result showed that each indicator, dimension, and construct met all the Goodness of Fit criteria (RMSEA < .08; CFI > .9). In addition, the value of Construct Reliability (CR) > .70 and Average Variance Extracted (AVE) > .50 were also obtained. Thus, the Sibling Conflict Strategy Scale can be used as a valid and reliable measurement to measure children’s sibling conflict strategies in Indonesia.